Recurrence of prostate cancer after HIFU. Proposal of a novel predictive index - Maestroni, Umberto; Morandin, Francesco; Ferretti, Stefania; Dinale, Francesco; Ziglioli, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Prostate cancer is one of the most common cancers in men over 50 years of age. Surgery, radiotherapy and hormonal manipulation represent its typical treatment. High-Intensity Focused Ultrasound (HIFU) is an alternative choice in localized prostate cancer. To date, an index for prediction of recurrence in patients treated with HIFU is not availabe. Our study proposes a novel index for the predition of recurrence able to determine if a candidate is fit for this tratment. methods: 107 patients underwent HIFU fram 2010 to 2015. A total of 12 variables were considered for the analysis. The final predictive model was obtained through a stepwise forward selection method. Results: The final model used a total of 6 variables, all correlated to the response variable. The Index is able to predict the recurrence after HIFU tratment in the most majority of candidates to treatment.  The index may be used to make a more scientific decision with regard to choosing optimal candidates for HIFU.